THE STANDARDS OF THE OFFICIAL DEALER IN THE AUTOMOTIVE BUSINESS - S. Gusev (Вестник университета)
Disassembled the highlights of the dealer system of identification, peculiarities of regulation of activities of the official dealer of the manufacturer.